Ольвійські погрудні теракоти з ліпними чашею і прикрасами - Шевченко, Т.М. (Археологія і давня історія України, 2018)
Проаналізовано погрудні жіночі зображення, прикрашені стефаною і сережками, знайдені
в Ольвії. Наявність ліпної чаші на голові виготовленої у формі фігурки, а також аналогії поза
Причорномор'ям уможливлюють трактувати їх
як погруддя-фіміатерії, що використовувались у релігійних культах. Analysed is a series of bust thymiateria with handmade
details: stephanes, earrings, and buttons fastening chiton on shoulders. Handmade cups on their heads
were not the headdress, but the functional details, and were probably used in some rituals as containers for incenses.
A detailed analysis shows that several of them were produced in a single mould, two items produced
not in Olbia, and on some of them tainia on the personage’s head were shown already in a mould. It is traced
that the busts are close to Olbian semi-figures of bigger size with more elaborate, though also handmade,
adorations. Stylistically, this group can be dated by the first half of the 3rd century BC. Almost all of them come
from the excavations at dwelling quarters and were probably used in family cults. They were often found
with other terracottas’ fragments, namely, with images of the Mother of the Gods and Dionysus.
These busts belong to one of several groups of Hellenistic thymiateria. They are the least definite for attribution.
Personages of other groups present the reliable features of their relation to the cults of the Mother
of the Gods, Aphrodite, and Dionysus. Similar thymiateria from other Ancient Greek centres represent images
of the same circle of the gods. Here, an attention to decorations and the clothes can only indirectly indicate
for an image of Aphrodite or a participant of her cult, while spherical adornments attached most often
to the temples, together with tainia on the heads of several items, can be hypothetically a part of a wreath
made of ivy fruits, as on the heads of Dionysiac characters. Consequently, there are no reliable grounds
yet for a definite attribution of these thymiateria’s images. There are also no grounds to see Demeter or
Kore-Persephone in them. The study of other groups of Olbian busts-thymiateria is perspective for the further attribution.